2001
DOI: 10.1021/cm0100063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Catalytic Properties of Pillared Montmorillonite with Aluminum/Cerium Polyoxycations

Abstract: This paper describes the preparation of pillared montmorillonite by means of mixed aluminum and cerium oligomers. When cerium was incorporated into the materials, the basal spacing increased up to 26 Å. Nuclear magnetic resonance studies indicated total absence of tetrahedral aluminum in the polyoxycations incorporated between the clay sheets. These results indicate that AlCe-pillared montmorillonite incorporates inorganic polyoxycations with a chemical nature different from that of the aluminum polyoxycation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Cerium (Ce) was introduced into pillared clays with Al and Al-Fe, improving the metallic dispersion properties, increasing the pillars resistance [124][125][126], and favoring the redox properties of the active metallic phase [48,127]. The catalysts obtained by the pillaring of Colombian bentonite with Al-Fe or Al-Ce-Fe are highly efficient for the reaction of phenol oxidation in diluted aqueous media in moderate conditions of temperature and pressure (25 • C and atmospheric pressure).…”
Section: Wet Hydrogen Peroxide Catalytic Oxidation (Whcpo)mentioning
confidence: 99%
“…Cerium (Ce) was introduced into pillared clays with Al and Al-Fe, improving the metallic dispersion properties, increasing the pillars resistance [124][125][126], and favoring the redox properties of the active metallic phase [48,127]. The catalysts obtained by the pillaring of Colombian bentonite with Al-Fe or Al-Ce-Fe are highly efficient for the reaction of phenol oxidation in diluted aqueous media in moderate conditions of temperature and pressure (25 • C and atmospheric pressure).…”
Section: Wet Hydrogen Peroxide Catalytic Oxidation (Whcpo)mentioning
confidence: 99%
“…Indeed, it has been shown that pillared clay with different basal spacing and microporosity was prepared with mixed cation pillaring [3][4][5][6][7]. In addition, previous works [7,8] report that the incorporation of species of Ce favors catalytic activity (CWPO reaction) of the pillared clays, probably because the cerium oxide formed in the solids enhances the textural properties of the solid, the dispersion and/or the redox properties of active species [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…From their first syntheses during the late 1970s, PILCs (pillared interlayered clays) have attracted a lot of attention and have been the subject of numerous studies. They are generated through the exchange of the small charge-compensating cations (usually alkali) of the clays, situated between the negatively charged clay layers, with metal polyoxycations. , Calcination at 400 °C or higher temperatures leads to the dehydration and dehydroxylation of hydroxycations and their conversion to metal oxide pillars separating the clay layers. ,, Hence, for example, pillaring a clay with Al implies first the intercalation of the Keggin ion [AlO 4 Al 12 (OH) 24 (H 2 O) 12 ] 7+ 8,9 and then the formation of Al 2 O 3 pillars as a result of heat treatment. …”
Section: Introductionmentioning
confidence: 99%
“…Pillaring of clay with metal oxides results in the appearance of new and interesting properties. First, the presence of these large pillars instead of alkali cations in the clay interlayer space causes the development of micropores (pores with a width smaller than 20 Å). ,, Another valuable feature of PILCs is their acidity, whether it is of the Brønsted or of the Lewis kind. Even though clays originally have Brønsted acidic character, introducing metal oxide pillars, especially aluminum, brings Lewis acid sites .…”
Section: Introductionmentioning
confidence: 99%